Dividend Smoothing and Determinants of Dividend Payout: Empirical Evidence from U.S. - Ye, Zhu (2012)
In this paper, it aims to find out whether the dividend policy is smoothing among the U.S. companies and investigates the driving factors behind the dividend increase and cut decision. At same time, it provides the comparison of three industries (Manufactory, Service and Retail) on dividend policy. All of these results are based on U.S. public quoted companies where are listed on the New York Stock Exchange (NYSE) and NASDAQ. The results from empirical can be summarized two parts. Firstly, through a test of Lintner Model (1956) and variation of this model, it shows that the U.S. companies always keep a smooth dividend policy and retail industry is smoother than other two industries. Secondly, from the results of logit analysis of the determinants of dividend increase and cut, it indicates that profitability and lagged asset significantly affect dividend increase and cut, while beta is only significant in dividend cut. Moreover, it finds the significant evidence that retail industry is higher level on dividend increase than other two industries. In overall, our results suggest that, compare to manufactory and service industry, retail industry has more stable and smoother dividend policy so that it has higher ability to give dividend increase and reduce the level of dividend cut.